Knowledge sharing: nurse managers' practices - Ana Lúcia Arcanjo Oliveira Cordeiro; Rosana Maria de Oliveira Silva; Josicélia Dumêt Fernandes; Gilberto Tadeu Reis da Silva (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objective: To analyze how management practices for sharing knowledge are developed in public hospitals in the context of nursing. Methods: Qualitative research, carried out with 15 nurse managers from six public hospitals, from July to September 2022. Data were collected through semi-structured interviews and analyzed according to content analysis and in a model for sharing knowledge at work. Results: Knowledge sharing in nursing occurs through intraand extra-organizational training (training, courses and events), use of digital communication tools (media and social networks) and individual and collective contact between professionals during the service (experiences, exchange of experiences and assessment feedback). Final considerations: Sharing knowledge is relevant to nursing work. To improve it, it must be understood that effective sharing occurs from person to person, in their daily practices, and must be conducted as a strategically planned process by nurse managers.